2009
DOI: 10.3758/mc.37.3.368
|View full text |Cite
|
Sign up to set email alerts
|

The effect of task and pitch structure on pitch-time interactions in music

Abstract: Musical pitch-time relations were explored by investigating the effect of temporal variation on musical pitch processing. In Experiment 1, musicians heard a standard tone, followed by a tonal context, then followed by a comparison tone, and performed one of two tasks. In the cognitive task, listeners were asked to ignore the standard tone and to judge whether the comparison tone was in the key of the context. In the perceptual task, listeners were asked to ignore the context and judge whether the comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 79 publications
(168 reference statements)
9
33
1
1
Order By: Relevance
“…In Experiment 1, using a standard probe sequence recognition paradigm, many participants reported using a visual strategy, favoring global matching procedures based on the comparison of contour-based relational shape patterns of the target and probe musical sequences [72] rather than storage of separated item representations and item-serial position associations. Previous experiments in musical cognition showed that the salience of a dimension such as pitch or temporal structure can prioritize the processing of one of them at the expense of the other [7678]. Providing full melodic context at encoding and recognition, as we did in Experiment 1, could therefore have prioritized the processing of global contour shape information, at the expense of detailed, item-based pitch processing.…”
Section: Discussionmentioning
confidence: 73%
“…In Experiment 1, using a standard probe sequence recognition paradigm, many participants reported using a visual strategy, favoring global matching procedures based on the comparison of contour-based relational shape patterns of the target and probe musical sequences [72] rather than storage of separated item representations and item-serial position associations. Previous experiments in musical cognition showed that the salience of a dimension such as pitch or temporal structure can prioritize the processing of one of them at the expense of the other [7678]. Providing full melodic context at encoding and recognition, as we did in Experiment 1, could therefore have prioritized the processing of global contour shape information, at the expense of detailed, item-based pitch processing.…”
Section: Discussionmentioning
confidence: 73%
“…When they have information about an upcoming event and it lasts longer than expected, they tend Downloaded by [University of Illinois Chicago] at 09:12 21 November 2014 240 The Journal of General Psychology to overestimate its actual duration. In the expectancy/contrast model of Jones and Boltz (1989), they suggest that when one attends to stimuli in an anticipatory fashion, the confirmation or violation of expected ending times exerts a systematic influence on duration judgments (Boltz, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In regards to the psychological variables, the following were found to be particularly relevant for inducing perceived time dilation: affective variables, motivation for the outcome, and time related expectancies (Angrilli, Cherubini, Pavese, & Manfredini, 1997;Boltz, 1993;Konig, 2005;Jones, 1988;Meade, 1963;Noulhiane, Mella, Samson, Ragot, & Pouthas, 2007).…”
Section: Factors That Affect Temporal Distortionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Melodic contour refers to the rising and falling pattern of intervals within a melody, and whether adjacent notes are higher or lower than one another [12]. The contour of a melody does not consider the precise size of successive pitch intervals, but represents the direction of pitch changes that occur throughout a sequence [13]. The psychological significance of contour has been underscored by findings that infants are sensitive to pitch contour but not other details of melodies [14], and that adults who hear a novel melody tend to remember its contour but not absolute pitches or precise pitch intervals [1519].…”
Section: Introductionmentioning
confidence: 99%